The Practice of Lesson Study Model in Teaching Writing Report Text - Sulastri Djumingin (Intelektual Pustaka Media Utama, 2017)
This study aimed at testing the effective use of the lesson study model to write report text from the observation performed by students at Junior High School level. This research was an experimental study with the posttest only control group design. The sampling technique was purposive sampling. The data were collected through test and observation. The results showed that the lesson study model is sufficient to be applied to write report text of observation for the Junior High School students. It is proven by the data that the value of tcalc= 16.087 more than value of t table = 1.67 on α 0.05 and degree of freedom= 58.